2011
DOI: 10.1590/s0104-42302011000400020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência estimada da doença renal crônica terminal em crianças no Estado de São Paulo

Abstract: The prevalence of 23.4 cases pmarp found by the authors is lower than that reported in Western world. We believe data were underestimated in the present study, as few dialysis units returned the completed questionnaire. This potential bias does not invalidate the exploratory character of results. Further mechanisms for retrospective and earlier data collecting on pediatric chronic renal disease (CRD) are needed so that the burden of this serious health condition can be appropriately sized up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
2
13
1
9
Order By: Relevance
“…Apesar de outras pesquisas realizadas no Brasil (7,11) apontarem predomínio do gênero masculino entre o público pediátrico com DRC, os resultados obtidos neste estudo não evidenciaram essa mesma supremacia, sendo que a distribuição de pacientes, segundo o gênero, foi de 50%. Por outro lado, a faixa etária predominante na presente pesquisa mostrou-se consoante ao apontado na literatura pertinente, bem como pela Associação Brasileira dos Centros de Diálise e Transplante, a qual descreve que pacientes com idade entre 10 e 15 anos apresentaram-se em maior número nos centros pediátricos de TRS do Brasil (12) .…”
Section: Discussionunclassified
“…Apesar de outras pesquisas realizadas no Brasil (7,11) apontarem predomínio do gênero masculino entre o público pediátrico com DRC, os resultados obtidos neste estudo não evidenciaram essa mesma supremacia, sendo que a distribuição de pacientes, segundo o gênero, foi de 50%. Por outro lado, a faixa etária predominante na presente pesquisa mostrou-se consoante ao apontado na literatura pertinente, bem como pela Associação Brasileira dos Centros de Diálise e Transplante, a qual descreve que pacientes com idade entre 10 e 15 anos apresentaram-se em maior número nos centros pediátricos de TRS do Brasil (12) .…”
Section: Discussionunclassified
“…A study conducted in São Paulo has estimated a prevalence of 23.4 cases per million in the population with compatible age (pmpca), and in Rio de Janeiro, in 2007, a prevalence of 24 cases pmpac was found -lower numbers when compared to the 84.6 cases pmpac of a similar study carried out the United States, and to the 62 cases pmpac reported in a European study, which included data on 12 countries [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Six studies conducted in Brazil were analyzed [4,11,13,16,20,23], being four quantitative and two qualitative. Among them, two were carried out in the Northeast, one in the South and three in the Southwest.…”
mentioning
confidence: 99%
“…Os dados epidemiológicos relacionados a IRC são em sua maioria concentrados em estudos direcionados a pacientes adultos, limitando a vantagem relacionada ao reconhecimento precoce da doença, quando esta ocorre em crianças e adolescentes (NOGUEIRA et al, 2011). Nessa faixa etária são poucos os estudos encontrados e quando a IRC é avaliada, já encontra-se muitas vezes em estágio avançado (NOGUEIRA et al, 2011).…”
Section: Crianças E Adolescentes Com Condições Crônicasunclassified
“…Nessa faixa etária são poucos os estudos encontrados e quando a IRC é avaliada, já encontra-se muitas vezes em estágio avançado (NOGUEIRA et al, 2011).…”
Section: Crianças E Adolescentes Com Condições Crônicasunclassified